2012
DOI: 10.1002/bmb.20611
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of multiple choice questions as a revision exercise at the end of a teaching module in biochemistry

Abstract: The graduate medical students often get less opportunity for clarifying their doubts and to reinforce their concepts after lecture classes. Assessment of the effect of MCQ preparation by graduate medical students as a revision exercise on the topic ''Mineral metabolism.'' At the end of regular teaching module on the topic ''Mineral metabolism,'' graduate medical students were asked to prepare the stems of 15 MCQs based on the four discriminators given for each. They were told that one of the discriminators cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Formulation of questions followed by small group discussion is an effective active revision exercise at the end of a teaching module in Biochemistry . We also found that formulation of multiple choice questions as an effective active learning process for the graduate medical students . Yet another active learning process which we had developed was Identification of mistakes and their correction by small group discussion .…”
Section: Introductionmentioning
confidence: 72%
“…Formulation of questions followed by small group discussion is an effective active revision exercise at the end of a teaching module in Biochemistry . We also found that formulation of multiple choice questions as an effective active learning process for the graduate medical students . Yet another active learning process which we had developed was Identification of mistakes and their correction by small group discussion .…”
Section: Introductionmentioning
confidence: 72%
“…An alternative approach is to shift the onus of formative question‐writing away from staff to students. Involving students in question‐writing may bring additional benefits, as writing and setting questions in various contexts is an effective method of learning …”
Section: Introductionmentioning
confidence: 99%
“…Based on comparisons of the preand post-test conditions, Stone concluded that students in both intervention groups did significantly better than the control group in the post-test condition, but neither group did well on retention as measured by the second post-test. Bobby et al (2012) compared the performance of students who were asked to reformulate multiple-choice questions in a biochemistry module individually and in small discussion groups. Although students' gains from the individual task and the small-group discussions were substantial, there was no advantage for either the individual or smallgroup discussion conditions, and this was true for various categories of students (low achievers, medium achievers, high achievers).…”
Section: The Effect Of Discussion On Student Learningmentioning
confidence: 99%